Analisis Tingkat Kepuasan Petugas Kesehatan terhadap Penggunaan Rekam Medis Elektronik - Tarigan, Raskhita Irena Debora; Lesmana, Hanry Anta; Pinem, Jeanika; Purba, Eka Permatasari (Lembaga Teewan Journal Solutions, 2026)
The implementation of Electronic Medical Records (EMR) is part of the digital transformation of healthcare services aimed at improving service quality, work efficiency, and the quality of health information management. The success of EMR implementation is not only determined by technological readiness but also influenced by the level of satisfaction of healthcare workers as system users. This study aims to analyze factors related to healthcare worker satisfaction in the use of EMR at the Darussalam Community Health Center (Puskesmas Darussalam). The study used an observational analytical design with a cross-sectional approach. The study sample consisted of 40 healthcare workers selected using a total sampling technique. Data were collected using a structured questionnaire that had met validity and reliability tests, then analyzed using the Chi-Square test with a significance level of 95%. The results showed that most respondents were aged 30–40 years (45.0%), were female (65.0%), had worked for 5–10 years (45.0%), and had attended EMR training (60.0%). Bivariate analysis showed that age (p=0.041) and history of EMR training (p=0.008) were significantly associated with healthcare worker satisfaction, while gender (p=0.321) and length of service (p=0.274) were not significantly associated. EMR training was shown to be the most significant contributing factor to user satisfaction. It was concluded that competency improvement through continuous training and improvements in the quality of systems and infrastructure are necessary to increase staff satisfaction and support the successful implementation of Electronic Medical Records in Community Health Centers.